PSYCHOLOGICAL FEATURES OF COMMUNICATION IN PRESCHOOL CHILDREN - Abdullaeva Nigora Rakhimovna; Yoqubjonova Yoqutxon Muzaffarjon qizi; Muhamadaliyeva Dinara Asrorjon qiz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents some psychological analyses of the characteristics of the communicative development of preschool children and the characteristics of communicative development.